Back Cover: Head‐to‐Tail Oligomerization by Silylene‐Tethered Sonogashira Coupling on Ag(111) (Angew. Chem. Int. Ed. 36/2021). Issue 36 (28th June 2021) - Sun, Kewei; Sagisaka, Keisuke; Peng, Lifen; Watanabe, Hikaru; Xu, Feng; Pawlak, Rémy; Meyer, Ernst; Okuda, Yasuhiro; Orita, Akihiro; Kawai, Shigeki
Abstract : Silylene‐tethered Sonogashira cross‐coupling enables the synthesis of partially fluorinated phenylene–ethynylene (PFPE) oligomers on Ag(111), as reported by Akihiro Orita, Shigeki Kawai, and co‐workers in their Communication on page 19598 . The desilylative Sonogashira reaction achieved a high chemoselectivity of up to 75 % while the competing Ullmann homocoupling and desilylative Glaser coupling were suppressed.